Photocatalytic Difluoromethylation Reactions of Aromatic Compounds and Aliphatic Multiple C-C Bonds - Barata Vallejo, Sebastian (2019)
Among the realm of visible light photocatalytic transformations, late-stagedifluoromethylation reactions (introduction of difluoromethyl groups in the last stages of syntheticprotocols) have played relevant roles as the CF2X group substitutions exert positive impacts on thephysical properties of organic compounds including solubility, metabolic stability, andlipophilicity, which are tenets of considerable importance in pharmaceutical, agrochemical, andmaterials science. Visible-light-photocatalyzed difluoromethylation reactions are shown to beaccomplished on (hetero)aromatic and carbon?carbon unsaturated aliphatic substrates under mildand environmentally benign conditions.